Existence of Solutions for a Viscoelastic Plate Equation with Variable Exponents and a General Source Term - Bouizem, Youcef; Alharbi, Asma; Boulaaras, Salah (Mathematics (Basel), 2024)
The subject of this study is a nonlinear viscoelastic plate equation with variable exponents and a general source term. Through the application of the Faedo–Galerkin approximation method and a fixed point theorem under appropriate assumptions, we proved the existence of weak solutions.